Determinants of the microfinance growth in selected countries / Nurafarina Razali and Nurul Amirah Ahmad - Razali, Nurafarina; Ahmad, Nurul Amirah (Faculty of Business and Management, 2018)
This study uses the data series of variable Interest rate, Inflation rate, Number of Microfinance Borrowers and Foreign Direct Investment (FDI) to measure the relationship of these five Economics variables towards the Microfinance growth. In addition, this study tries to investigate the best model to use among Panel Regression Fixed Effect, Panel Regression Random Effect and Pooled OLS Test. This study also applies a panel data procedure and the sample of this study is taken by yearly from year 2004 until 2016 in 9 selected countries which are Brazil, Bolivia, Bangladesh, Mexico, Moldova, Ukraine, Nigeria, Nicaragua and South Africa. The findings of this study show there is a significant negative relationship between Microfinance growth and Interest rate. There is a significant positive relationship between Microfinance growth and Inflation rate. There is a significant negative relationship between Microfinance growth and Number of Microfinance Borrowers. Lastly, there is a significant positive relationship between Microfinance growth and Foreign Direct Investment (FDI).